The influence of language and culture on a South African corporate (Communicare: Journal for Communication Studies in Africa, 2022)
This study investigates whether the different home languages of the employees in a SouthAfrican corporate have an influence on their perception of the organisational structureand processes. The study was conducted in the context of the ABSA financial institutionin the Western Cape.The authors conducted a series of interviews with management-level employees whospeak Afrikaans, English and Xhosa as home languages, in an attempt to ascertain theextent of the influence of individual cultures on perceptions and actions in corporatesociety. Specific attention was given to how these individuals perceived meetings,decision-making processes and conflict.These interviews were transcribed verbatim and studied by means of narrative analysisusing a specialised software package to provide better insight into the roles that languageand culture play in a South African organisation. Based on the narratives provided by therespondents in this study, the authors concluded that individual culture plays a significantrole in the perceptions of organisational structures such as conflict management,interaction during meetings, decision-making and the acceptance of authority.South Africa is now celebrating more than ten years of democracy following the country’sfirst democratic election in 1994. In the past decade, corporate South Africa has seenan unprecedented cultural diversity in its workforce. The dynamics of local organisationshave changed to incorporate the various cultural representations. In an attempt to explorethe multicultural phenomenon that exists in the workplace, the authors conducted astudy among the supervisory and managerial staff of a prominent South African financialinstitution, ABSA, in the hope of providing better insight into the roles language andculture play in a South African organisation. Such an understanding could not onlyestablish a more effective organisational culture, but also ultimately help South Africanbusiness to deal with cultural diversity and conflict in the workplace in a more creativeway. This article describes a qualitative research project utilising narrative analysis toinvestigate how employees’ home language influences their perception of corporateculture.